2020
DOI: 10.3390/molecules25184318
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Bioactivity Evaluation of 4,6-Disubstituted Pyrido[3,2-d]pyrimidine Derivatives as Mnk and HDAC Inhibitors

Abstract: Both HDACs and Mnks play important role in translating multiple oncogenic signaling pathways during oncogenesis. As HDAC and Mnk are highly expressed in a variety of tumors; thus simultaneous inhibit HDAC and Mnk can increase the inhibition of tumor cell proliferation and provide a new way of inhibiting tumor growth. Based on the previous work and the merge pharmacophore method; we designed and synthesized a series of 4,6-disubstituted pyrido[3,2-d]pyrimidine derivatives as HDAC and Mnk dual inhibitors. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Frontiers in Chemistry frontiersin.org Frontiers in Chemistry frontiersin.org can be seen that three ligands showed similar patterns of binding to the protein with a small difference in the number of H-bonds. These interaction patterns were also consistent with the results of several studies; H-bond with amino acid MET162 was described by K. Xing et al, and X. Jin et al, (Jin et al, 2019;Xing et al, 2020). Hydrophobic interactions with VAL98, ALA111, LEU168, and LEU212 were reported by S. Wang et al (Wang et al, 2018) On the other hand, the three ligands interacted with the PIM-2 as shown in Figure 4.…”
Section: Figuresupporting
confidence: 90%
“…Frontiers in Chemistry frontiersin.org Frontiers in Chemistry frontiersin.org can be seen that three ligands showed similar patterns of binding to the protein with a small difference in the number of H-bonds. These interaction patterns were also consistent with the results of several studies; H-bond with amino acid MET162 was described by K. Xing et al, and X. Jin et al, (Jin et al, 2019;Xing et al, 2020). Hydrophobic interactions with VAL98, ALA111, LEU168, and LEU212 were reported by S. Wang et al (Wang et al, 2018) On the other hand, the three ligands interacted with the PIM-2 as shown in Figure 4.…”
Section: Figuresupporting
confidence: 90%
“…Among the different DTQ analogues, compound ( 4 ) showed the most promising results, that may be due to the addition of 4-fluoroaniline. In fact, adding 4-fluoroaniline can increase the hydrophobicity, bulkiness and anti-proliferative activity of the compound [ 18 , 51 ]. Yet to confirm the findings, in vitro experimental analysis is warranted.…”
Section: Resultsmentioning
confidence: 99%
“… 97 Another group designed 4,6-disubstituted pyrido[3,2-d]pyrimidine derivatives that target both MNK and histone deacetylase (HDAC) which inhibited prostate cancer cell growth and could be tested in leukemia cells since HDAC inhibitors are also being explored individually in leukemia. 98 , 99 The effectiveness of these dual inhibitors could be related to the links of MNKs to overcoming resistance as mentioned in the previous section.…”
Section: Preclinical Combination Studies Using Mnk Inhibitorsmentioning
confidence: 99%